A gradient bionic dental restoration material and preparation method thereof
By designing gradient structure and optimizing raw material combination, combining silane coupling agent treatment and resin penetration technology, the problem of uniform mechanical properties and aesthetic properties of existing dental restoration materials is solved, and the gradient mechanical properties and flexibility of the material is combined, which is suitable for Dental restoration.
Patent Information
- Application Number
- CN202310055619.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-19
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-01-19
AI Technical Summary
The mechanical properties and aesthetic properties of existing dental restoration materials are uniform, and the gradient mechanical properties and gradient aesthetic properties of natural teeth cannot be effectively biomimetic. Moreover, the porosity of porous ceramic frames after using 3D printing technology leads to poor material strength and elastic modulus. .
Using gradient bionic dental restoration materials, by designing gradient structures and optimizing raw material combinations, combining polymeric monomers and multi-layer porous composite ceramic skeletons, silane coupling agent treatment and resin penetration technology, a polymer matrix with gradient mechanical properties is formed. Permeable ceramic composite material.
The gradient changes in the mechanical properties of the material are achieved, ensuring equal wear of the restoration and the jaw teeth, while avoiding impact on the contact surface of the natural teeth, combining the flexibility of the resin material and the rigidity of the ceramic material.
Smart Images

Figure BDA0004060508090000141 
Figure BDA0004060508090000171 
Figure BDA0004060508090000181
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of dental restoration, and in particular relates to a gradient bionic dental restoration material and a preparation method thereof. Background Art
[0002] Resin-ceramic composite material is a machinable material that simulates the properties of natural teeth. It combines the high strength of ceramic materials with the good toughness and aesthetic effects of resin materials. It is widely used in crowns, veneers, inlays and onlays, as well as implant crowns.
[0003] Resin ceramic composite materials can be divided into two categories according to the process:
[0004] (1) With resin as the matrix, an organic resin material and an inorganic ceramic material that has been coupled are mixed and then cured; for example, CN107903557A discloses a cuttable resin-infiltrated glass ceramic material for dental restoration. This patent prepares the material by mixing barium silanized glass ceramic powders of different particle sizes and a colorant and pressing them into a porous block ceramic body. The resin matrix is completely infiltrated into the porous ceramic body under vacuum conditions, and the resultant is cured under high temperature and high pressure conditions. This method solves the technical problems of uneven component distribution and unsatisfactory cutting performance of existing materials, and enables the worthy material to have a good double interpenetrating cross-linked network structure of resin and ceramic, and has excellent cutting performance. However, the discontinuous ceramic skeleton structure of this type of composite material makes the mechanical properties of the material, such as elastic modulus and wear resistance, relatively low, and the performance is close to that of dentin;
[0005] (2) Using ceramic as the matrix, pre-sintering the inorganic ceramic material into a porous ceramic body, and then infiltrating the resin into the porous ceramic body and curing it; for example, CN108578250A discloses a resin-infiltrated silicate composite material for dental restoration, wherein a partially sintered porous ceramic block is prepared by controlling the sintering temperature and the holding time, and then the resin is infiltrated into the partially sintered porous ceramic block by vacuum capillary action, and then a silicate / resin double network structure is formed after a curing reaction. This type of resin-infiltrated ceramic composite material effectively combines the advantages of resin and ceramic, and at the same time has higher mechanical properties and aesthetic properties. However, the mechanical properties and aesthetic properties of natural teeth vary in a gradient, while the mechanical properties and aesthetics of this type of restorative material are uniform, with a high elastic modulus, high hardness, and performance close to that of tooth enamel, and cannot mimic the gradient mechanical properties and gradient aesthetic properties of natural teeth. CN114213021A discloses a gradient bionic dental ceramic, which uses 3D printing technology to print a porous ceramic frame with a TPMS structure and a porosity that gradually increases from top to bottom, and the synthetic resin penetrates into the mesh through holes through capillary action, achieving gradient mechanical properties and gradient gradual effects. However, when the porous ceramic frame is printed using 3D printing technology, light curing is used to print a green piece with mesh through holes, so the solid content of the green piece is low, and the porosity of the porous ceramic frame obtained after sintering is large, resulting in poor mechanical properties such as strength, elastic modulus hardness, etc. of the material.
[0006] In summary, how to provide a polymer-infiltrated ceramic material that can achieve gradient changes in mechanical properties so that the restoration and the opposing teeth can be worn equally without causing impact on the contact surface with the natural teeth has become a problem that needs to be solved urgently. Summary of the invention
[0007] In view of the problems existing in the prior art, the purpose of the present invention is to provide a gradient bionic dental restoration material and a preparation method thereof. The gradient bionic dental restoration material combines the flexibility of resin materials and the rigidity of ceramic materials through the design of gradient structure and the optimization of raw materials, so that the restoration and the opposing teeth are worn equally without causing impact on the contact surface with the natural teeth.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a gradient bionic dental restoration material, wherein the raw materials of the gradient bionic dental restoration material include a polymerizable monomer, a multi-layer porous composite ceramic skeleton and an initiator;
[0010] The weight ratio of the polymerizable monomer to the multilayer porous composite ceramic skeleton is 10:90 to 90:10, for example, 10:90, 20:80, 30:70, 40:60, 50:50, 60:40, 70:30, 80:20 or 10:90, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 12:88 to 30:70;
[0011] The weight of the initiator is 0.01 to 10 wt% of the weight of the polymerizable monomer, such as 0.01 wt%, 0.1 wt%, 1 wt%, 2 wt%, 4 wt%, 6 wt%, 8 wt% or 10 wt%, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable, preferably 0.1 to 3 wt%;
[0012] The multi-layer porous composite ceramic skeleton is composed of at least two layers, and the mechanical properties gradually increase from the dentin to the enamel.
[0013] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0014] As a preferred technical solution of the present invention, the polymerizable monomer includes a free radical resin monomer.
[0015] Preferably, the free radical resin monomer includes methyl (meth)acrylate, isobutyl (meth)acrylate, benzyl (meth)acrylate, dodecyl (meth)acrylate, 2-(N,N-dimethylamino)ethyl (meth)acrylate, 2,3-dibromopropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, propylene glycol mono(meth)acrylate, glycerol mono(meth)acrylate, erythritol mono(meth)acrylate, N-hydroxymethyl (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, N-(dihydroxyethyl) (meth)acrylamide, (Meth)acryloyloxydodecylpyridinium bromide, (meth)acryloyloxydodecylpyridinium chloride, (meth)acryloyloxyhexadecylpyridinium chloride, (meth)acryloyloxydecyl ammonium chloride, 2-(meth)acryloyloxyethyl dihydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 2-(meth)acryloyloxyethylphenyl hydrogen phosphate, 11-(meth)acryloyloxy-1,1-undecanedicarboxylic acid, 4-(meth)acryloyloxyethoxycarbonylphthalic acid, 10-mercaptodecyl (meth)acrylate, ethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate , neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, bisphenol A diglycidyl (meth)acrylate (2,2-bis[4-[3-(meth)acryloyloxy-2-hydroxypropoxy]phenyl]propane), 2,2-bis[4-(meth)acryloyloxyethoxyphenyl]propane, 2,2-bis[4-(meth)acryloyloxypolyethoxyphenyl]propane, 1,2-bis[3-(meth)acryloyloxy-2-hydroxypropoxy]ethane, pentaerythritol di(meth)acrylate, [2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl) ] dimethacrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, bisphenol A dimethacrylate (2-methyl-2-acrylic acid-(1-methylethylidene)bis(4,1-phenylene)diester), N,N'-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxyl)propane-1,3-diol]tetramethacrylate or 1,7-diacryloyloxy-2,2,6,6-tetraacryloyloxymethyl-4-oxyheptane, any one or a combination of at least two thereof.
[0016] As a preferred technical solution of the present invention, the initiator includes any one of dicumyl peroxide, tert-butyl peroxide, benzoyl peroxide, tert-butyl peracetate, isopropylbenzene peroxide, methyl ethyl ketone peroxide or tert-butyl perbenzoate, or a combination of at least two thereof. Typical but non-limiting examples of the combination include a combination of tert-butyl peroxide and benzoyl peroxide, a combination of isopropylbenzene peroxide and benzoyl peroxide, and the like.
[0017] As a preferred technical solution of the present invention, the multi-layer porous composite ceramic skeleton is treated with a silane coupling agent to obtain a modified multi-layer porous composite ceramic skeleton.
[0018] As a preferred technical solution of the present invention, the gradient bionic dental restoration material further includes additives.
[0019] Preferably, the additive comprises any one of a crosslinking agent, a fluorescent agent, a bactericide, a colorant, a promoter, an inhibitor, an ultraviolet absorber, an anti-discoloration agent, a viscosity regulator, a wetting agent, an antioxidant, a stabilizer or a diluent, or a combination of at least two thereof. Typical but non-limiting examples of the combination include: a combination of a fluorescent agent, a bactericide and a colorant, a combination of an anti-discoloration agent, a viscosity regulator and a wetting agent, etc.
[0020] Preferably, the amount of the additive added is 0 to 5 wt% of the total weight of the polymerizable monomer and the multilayer porous composite ceramic skeleton, for example 0 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt% or 5 wt%, etc., but is not limited to the listed values. Other unlisted values within this numerical range are also applicable, preferably 0.01 to 1 wt%.
[0021] Preferably, in terms of weight percentage, the physical phases of the multilayer porous composite ceramic skeleton include 5 to 70 wt% glass phase, for example, 5 wt%, 10 wt%, 20 wt%, 40 wt%, 60 wt% or 70 wt%; 5 to 60 wt% feldspar phase, for example, 5 wt%, 10 wt%, 20 wt%, 40 wt% or 60 wt%; 5 to 40 wt% zirconia phase, for example, 5 wt%, 10 wt%, 20 wt% or 40 wt%; the selection of the above values is not limited to the listed values, and other unlisted values within their respective numerical ranges are equally applicable.
[0022] In a second aspect, the present invention provides a method for preparing the gradient bionic dental restoration material according to the first aspect, the preparation method comprising the following steps:
[0023] (1) mixing an inorganic filler, a pore-forming agent and a binder to obtain at least two mixed raw materials; wherein the inorganic filler component ratio in each mixed raw material is different;
[0024] (2) performing a first dry pressing on each of the obtained mixed raw materials independently to obtain a green body; then stacking each green body in sequence, performing a second dry pressing, cold isostatic pressing and sintering in sequence to obtain a multi-layer porous composite ceramic skeleton;
[0025] (3) impregnating the obtained multi-layer porous composite ceramic skeleton with a silane coupling agent solution to obtain a modified multi-layer porous composite ceramic skeleton;
[0026] (4) infiltrating the obtained modified multilayer porous composite ceramic skeleton with resin to obtain a resin-infiltrated composite ceramic skeleton;
[0027] (5) The obtained resin-infiltrated composite ceramic skeleton is cured to obtain a polymer-based infiltrated ceramic composite material.
[0028] In the present invention, by using a silane coupling agent to modify the multi-layer porous composite ceramic skeleton, the chemical bonding between the inorganic filler and the resin monomer can be achieved, thereby improving the mechanical strength of the cured product.
[0029] As a preferred technical solution of the present invention, the inorganic filler in step (1) includes any one or a combination of at least two of silicon dioxide, aluminum silicate, sodium aluminosilicate, sodium silicate, potassium silicate, barium silicate, zirconium silicate, aluminum oxide, titanium dioxide, zirconium oxide, fluorine glass, borosilicate glass, sodium glass, barium glass, barium aluminosilicate glass, glass containing strontium or zirconium, glass ceramics, fluoroaluminosilicate glass, fumed silica, calcium fluoride, strontium fluoride, calcium carbonate, titanium oxide, calcium phosphate, hydroxyapatite, calcium hydroxide, strontium hydroxide, albite or potassium feldspar. Typical but non-limiting examples of the combination include: a combination of zirconium oxide and sodium aluminosilicate, a combination of zirconium oxide and glass ceramics, a combination of sodium aluminum silicate and glass ceramics, etc.
[0030] Preferably, the pore-forming agent comprises any one of polyvinyl alcohol, polyvinyl acetate, polyvinyl butyral, polymethyl methacrylate microspheres, polystyrene microspheres or starch, or a combination of at least two thereof. Typical but non-limiting examples of the combination include a combination of polyvinyl alcohol and polyvinyl acetate, a combination of polymethyl methacrylate microspheres and polystyrene microspheres, and the like.
[0031] Preferably, the raw materials in step (1) are respectively ball-milled and dried in sequence after being mixed to obtain at least two mixed raw materials.
[0032] Preferably, the rotation speed of the ball mill is 100 to 900 r / min, for example, 100 r / min, 200 r / min, 300 r / min, 500 r / min, 700 r / min or 900 r / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] Preferably, the ball milling time is 0.5-12 h, for example 0.5 h, 1 h, 2 h, 4 h, 6 h, 8 h, 10 h or 12 h, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, the drying temperature is 50-110°C, for example 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or 110°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the drying time is 12 to 24 hours, such as 12 hours, 16 hours, 20 hours or 24 hours, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0036] As a preferred technical solution of the present invention, the pressure of the first dry pressing in step (2) is 2 to 5 MPa, for example 2 MPa, 3 MPa, 4 MPa or 5 MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] Preferably, the time of the first dry pressing in step (2) is 10 to 60 seconds, for example 10 seconds, 20 seconds, 30 seconds, 40 seconds, 50 seconds or 60 seconds, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0038] Preferably, the blanks in step (2) are stacked in a manner such that the mechanical properties gradually increase from dentin to enamel.
[0039] Preferably, the pressure of the second dry pressing in step (2) is 4 to 10 MPa, for example 4 MPa, 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa or 10 MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] Preferably, the time of the second dry pressing in step (2) is 10 to 60 seconds, for example 10 seconds, 20 seconds, 30 seconds, 40 seconds, 50 seconds or 60 seconds, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0041] Preferably, the pressure of the cold isostatic pressing in step (2) is 150-300 MPa, for example, 150 MPa, 180 MPa, 200 MPa, 230 MPa, 280 MPa or 300 MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] Preferably, the time of the cold isostatic pressing in step (2) is 0.5 to 10 min, for example, 0.5 min, 1 min, 1.5 min, 2 min, 2.5 min, 3 min, 3.5 min, 4 min, 4.5 min, 5 min, 5.5 min, 6 min, 6.5 min, 7 min, 7.5 min, 9 min or 10 min, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0043] Preferably, the sintering in step (2) includes a first sintering and a second sintering performed sequentially.
[0044] Preferably, the heating rate of the first sintering is 2 to 10°C / min, for example, 2°C / min, 4°C / min, 6°C / min, 8°C / min or 10°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] Preferably, the first sintering temperature is 450-650°C, such as 450°C, 500°C, 550°C, 600°C or 650°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0046] Preferably, the first sintering holding time is 0.5 to 3 h, such as 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] Preferably, the heating rate of the second sintering is 2 to 10°C / min, for example, 2°C / min, 4°C / min, 6°C / min, 8°C / min or 10°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] Preferably, the second sintering temperature is 700-1300°C, for example 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1100°C, 1200°C or 1300°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] Preferably, the holding time of the second sintering is 0.5 to 5 h, for example, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 4 h or 5 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] In the present invention, a high-performance gradient bionic dental restoration material is obtained through the coordinated control of two dry pressings, cold isostatic pressing and sintering conditions, which meets people's requirements for dental restoration and has good application prospects.
[0051] As a preferred technical solution of the present invention, the immersion of the silane coupling agent solution in step (3) is carried out under vacuum conditions.
[0052] Preferably, in step (3), the multi-layer porous composite ceramic skeleton is impregnated with a silane coupling agent solution and then dried to obtain a modified multi-layer porous composite ceramic skeleton.
[0053] As a preferred technical solution of the present invention, the resin liquid used for the resin infiltration in step (4) includes a polymerizable monomer and an initiator.
[0054] Preferably, the resin liquid used for the resin infiltration in step (4) also includes additives.
[0055] Preferably, the resin infiltration in step (4) is carried out alternately under vacuum conditions and normal pressure (atmospheric pressure), and the operation is repeated multiple times to ensure that the resin completely penetrates the ceramic skeleton.
[0056] Preferably, the holding time of the resin penetration under vacuum conditions in step (4) is independently 10 to 60 minutes, for example 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes or 60 minutes, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] Preferably, the holding time of the resin penetration at normal pressure in step (4) is independently 10 to 60 minutes, for example 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes or 60 minutes, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] Preferably, the temperature of the curing treatment in step (5) is 60-180°C, for example 60°C, 80°C, 100°C, 120°C, 140°C, 160°C or 180°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] Preferably, the pressure of the curing treatment in step (5) is 100-300 MPa, for example, 100 MPa, 150 MPa, 200 MPa, 250 MPa or 300 MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] Preferably, the curing treatment time in step (5) is 1 to 10 hours, for example 1 hour, 2 hours, 3 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0061] Compared with the prior art, the present invention has the following beneficial effects:
[0062] The gradient bionic dental restoration material described in the present invention utilizes a multi-layer porous composite ceramic skeleton with a gradient structure close to that of natural teeth, and optimizes the selection of raw materials, as well as regulates the preparation conditions of each step, so that the material combines the flexibility of resin materials and the rigidity of ceramic materials. The resulting restoration and the opposing teeth achieve equal wear without causing impact on the contact surface with the natural teeth. DETAILED DESCRIPTION
[0063] In order to better illustrate the present invention and facilitate understanding of the technical solution of the present invention, the present invention is further described in detail below. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0064] In a specific embodiment, the present invention provides a gradient bionic dental restoration material, wherein the raw materials of the gradient bionic dental restoration material include a polymerizable monomer, a multi-layer porous composite ceramic skeleton and an initiator;
[0065] The weight ratio of the polymerizable monomer to the multi-layer porous composite ceramic skeleton is 10:90 to 90:10;
[0066] The weight of the initiator is 0.01 to 10 wt% of the weight of the polymerizable monomer;
[0067] The multi-layer porous composite ceramic skeleton is composed of at least two layers, and the mechanical properties gradually increase from the dentin to the enamel.
[0068] Further, the polymerizable monomer includes a free radical resin monomer;
[0069] Further, the free radical resin monomer includes methyl (meth)acrylate, isobutyl (meth)acrylate, benzyl (meth)acrylate, dodecyl (meth)acrylate, 2-(N,N-dimethylamino)ethyl (meth)acrylate, 2,3-dibromopropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, propylene glycol mono(meth)acrylate, glycerol mono(meth)acrylate, erythritol mono(meth)acrylate, N-hydroxymethyl (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, N-(dihydroxyethyl) (meth)acrylamide , (meth)acryloyloxydodecylpyridinium bromide, (meth)acryloyloxydodecylpyridinium chloride, (meth)acryloyloxyhexadecylpyridinium chloride, (meth)acryloyloxydecyl ammonium chloride, 2-(meth)acryloyloxyethyl dihydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 2-(meth)acryloyloxyethylphenyl hydrogen phosphate, 11-(meth)acryloyloxy-1,1-undecanedicarboxylic acid, 4-(meth)acryloyloxyethoxycarbonylphthalic acid, 10-mercaptodecyl (meth)acrylate, ethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate Ester, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, bisphenol A diglycidyl (meth)acrylate (2,2-bis[4-[3-(meth)acryloyloxy-2-hydroxypropoxy]phenyl]propane), 2,2-bis[4-(meth)acryloyloxyethoxyphenyl]propane, 2,2-bis[4-(meth)acryloyloxypolyethoxyphenyl]propane, 1,2-bis[3-(meth)acryloyloxy-2-hydroxypropoxy]ethane, pentaerythritol di(meth)acrylate, [2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl) ] dimethacrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, bisphenol A dimethacrylate (2-methyl-2-acrylic acid-(1-methylethylidene)bis(4,1-phenylene)diester), N,N'-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxyl)propane-1,3-diol]tetramethacrylate or 1,7-diacryloyloxy-2,2,6,6-tetraacryloyloxymethyl-4-oxyheptane, any one or a combination of at least two thereof.
[0070] Further, the initiator includes any one of dicumyl peroxide, tert-butyl peroxide, benzoyl peroxide, tert-butyl peracetate, cumene peroxide, methyl ethyl ketone peroxide or tert-butyl perbenzoate, or a combination of at least two thereof.
[0071] Furthermore, the multi-layer porous composite ceramic skeleton is treated with a silane coupling agent to obtain a modified multi-layer porous composite ceramic skeleton.
[0072] Furthermore, the gradient bionic dental restoration material also includes additives;
[0073] Further, the additive includes any one or a combination of at least two of a crosslinking agent, a fluorescent agent, a bactericide, a colorant, a promoter, an inhibitor, an ultraviolet absorber, an anti-discoloration agent, a viscosity modifier, a wetting agent, an antioxidant, a stabilizer or a diluent;
[0074] Furthermore, the amount of the additive added is 0-5wt% of the total weight of the polymerizable monomer and the multi-layer porous composite ceramic skeleton, preferably 0.01-1wt%.
[0075] In a specific embodiment, the present invention also provides a method for preparing the above-mentioned gradient bionic dental restoration material, the preparation method comprising the following steps:
[0076] (1) weighing a pore-forming agent, a binder, and an inorganic filler having different component ratios, mixing the mixed materials, and then ball milling the mixed materials with zirconium beads at a speed of 100 to 900 r / min for 0.5 to 12 h; and then drying the mixed materials at 50 to 110° C. for 12 to 24 h to prepare at least two layers of mixed raw materials;
[0077] Wherein, the inorganic filler includes any one of silicon dioxide, aluminum silicate, sodium aluminosilicate, sodium silicate, potassium silicate, barium silicate, zirconium silicate, aluminum oxide, titanium dioxide, zirconium oxide, fluorine glass, borosilicate glass, sodium glass, barium glass, barium aluminosilicate glass, glass containing strontium or zirconium, glass ceramics, fluoroaluminosilicate glass, fumed silica, calcium fluoride, strontium fluoride, calcium carbonate, titanium oxide, calcium phosphate, hydroxyapatite, calcium hydroxide, strontium hydroxide, albite or potassium feldspar, or a combination of at least two thereof;
[0078] The pore-forming agent includes any one of polyvinyl alcohol, polyvinyl acetate, polyvinyl butyral, polymethyl methacrylate microspheres, polystyrene microspheres or starch, or a combination of at least two thereof;
[0079] (2) Each mixed raw material is independently subjected to a first dry pressing at a pressure of 2 to 5 MPa and a holding time of 10 to 60 seconds to obtain a green body; each green body is then stacked according to the rule that the mechanical properties gradually increase in the direction from dentin to enamel, and then subjected to a second dry pressing at a pressure of 4 to 10 MPa and a holding time of 10 to 60 seconds; then subjected to cold isostatic pressing at a pressure of 150 to 300 MPa and a holding time of 0.5 to 10 minutes; finally subjected to sintering treatment, the sintering process is as follows: heating to 450 to 650°C at a heating rate of 2 to 10°C / min, and keeping the temperature for 0.5 to 3 hours; then heating to 700 to 1300°C at a heating rate of 2 to 10°C / min, and keeping the temperature for 0.5 to 5 hours, to obtain a multilayer porous composite ceramic skeleton;
[0080] (3) impregnating the obtained multi-layer porous composite ceramic skeleton with a silane coupling agent solution under vacuum conditions, and then drying to obtain a modified multi-layer porous composite ceramic skeleton;
[0081] (4) preparing a resin liquid, and alternately infiltrating the obtained modified multilayer porous composite ceramic skeleton with the resin liquid under vacuum conditions and normal pressure to obtain a resin-infiltrated composite ceramic skeleton;
[0082] (5) The obtained resin-infiltrated composite ceramic skeleton is cured at 60-180° C. and 100-300 MPa for 1-10 h to obtain a polymer-based infiltrated ceramic composite material.
[0083] The following are typical but non-limiting embodiments of the present invention:
[0084] Embodiment 1:
[0085] This embodiment provides a gradient bionic dental restoration material, based on the gradient bionic dental restoration material in a specific embodiment, wherein:
[0086] The weight ratio of the polymerizable monomer to the multi-layer porous composite ceramic skeleton is 20:80;
[0087] The weight of the initiator is 1wt% of the weight of the polymerizable monomer;
[0088] The multi-layer porous composite ceramic skeleton is composed of a three-layer structure, and the mechanical properties gradually increase from the dentin to the enamel;
[0089] The polymerizable monomers are bisphenol A diglycidyl (meth)acrylate and triethylene glycol dimethacrylate, with a mass ratio of 60:40;
[0090] The initiator is benzoyl peroxide;
[0091] The multi-layer porous composite ceramic skeleton is treated with a silane coupling agent (γ-methacryloxypropyltrimethoxysilane, KH-570) to obtain a modified multi-layer porous composite ceramic skeleton;
[0092] No additives.
[0093] The raw materials of the multi-layer porous composite ceramic skeleton are shown in Table 1.
[0094] Table 1
[0095] The first layer of inorganic filler Yttrium stabilized zirconium dioxide and lithium disilicate, mass ratio 3:7 The second layer of inorganic filler Yttrium stabilized zirconium dioxide and lithium disilicate, mass ratio 5:5 The third layer of inorganic filler Yttrium stabilized zirconium dioxide and lithium disilicate, mass ratio 8:2
[0096] Note: The layers are stacked one after another in the direction from dentin to enamel.
[0097] Embodiment 2:
[0098] This embodiment provides a gradient bionic dental restoration material, based on the gradient bionic dental restoration material in a specific embodiment, wherein:
[0099] The weight ratio of the polymerizable monomer to the multi-layer porous composite ceramic skeleton is 30:70;
[0100] The weight of the initiator is 1wt% of the weight of the polymerizable monomer;
[0101] The multi-layer porous composite ceramic skeleton is composed of a five-layer structure, and the mechanical properties gradually increase from the dentin to the enamel.
[0102] The polymerizable monomers are bisphenol A diglycidyl (meth)acrylate and triethylene glycol dimethacrylate, with a mass ratio of 60:40;
[0103] The initiator is benzoyl peroxide;
[0104] The multi-layer porous composite ceramic skeleton is treated with a silane coupling agent (γ-methacryloxypropyltrimethoxysilane, KH-570) to obtain a modified multi-layer porous composite ceramic skeleton;
[0105] No additives.
[0106] Among them, the raw materials of the multi-layer porous composite ceramic skeleton are shown in Table 2.
[0107] Table 2
[0108]
[0109] Note: The layers are stacked one after another in the direction from dentin to enamel.
[0110] Embodiment 3:
[0111] This embodiment provides a gradient bionic dental restoration material, based on the gradient bionic dental restoration material in a specific embodiment, wherein:
[0112] The weight ratio of the polymerizable monomer to the multi-layer porous composite ceramic skeleton is 25:75;
[0113] The weight of the initiator is 1.3 wt% of the weight of the polymerizable monomer;
[0114] The multi-layer porous composite ceramic skeleton is composed of a four-layer structure, and the mechanical properties gradually increase from the dentin to the enamel;
[0115] The polymerizable monomers are ethylene glycol di(meth)acrylate and [2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)]dimethacrylate, with a mass ratio of 30:70;
[0116] The initiator is dicumyl peroxide;
[0117] The multi-layer porous composite ceramic skeleton is treated with a silane coupling agent (γ-methacryloxypropyltrimethoxysilane, KH-570) to obtain a modified multi-layer porous composite ceramic skeleton;
[0118] No additives.
[0119] Among them, the raw materials of the multi-layer porous composite ceramic skeleton are shown in Table 3.
[0120] Table 3
[0121] The first layer of inorganic filler Alumina and lithium disilicate, mass ratio 3:7 The second layer of inorganic filler Alumina and lithium disilicate, mass ratio 4:6 The third layer of inorganic filler Alumina and lithium disilicate, mass ratio 5:5 The fourth layer of inorganic filler Alumina and lithium disilicate, mass ratio 6:4
[0122] Note: The layers are stacked one after another in the direction from dentin to enamel.
[0123] Embodiment 4:
[0124] This embodiment provides a gradient bionic dental restoration material, based on the gradient bionic dental restoration material in a specific embodiment, wherein:
[0125] The weight ratio of the polymerizable monomer to the multi-layer porous composite ceramic skeleton is 30:70;
[0126] The weight of the initiator is 0.5wt% of the weight of the polymerizable monomer;
[0127] The multi-layer porous composite ceramic skeleton is composed of a three-layer structure, and the mechanical properties gradually increase from the dentin to the enamel;
[0128] The polymerizable monomers are 2-methyl-2-acrylic acid-(1-methylethylene)bis(4,1-phenylene) diester, bisphenol A dimethacrylate and triethylene glycol dimethacrylate, with a mass ratio of 60:20:20;
[0129] The initiator is dicumyl peroxide;
[0130] The multi-layer porous composite ceramic skeleton is treated with a silane coupling agent (γ-methacryloxypropyltriethoxysilane) to obtain a modified multi-layer porous composite ceramic skeleton;
[0131] No additives.
[0132] Among them, the raw materials of the multi-layer porous composite ceramic skeleton are shown in Table 4.
[0133] Table 4
[0134] The first layer of inorganic filler Alumina, lithium disilicate and feldspar, mass ratio 3:4:4 The second layer of inorganic filler Alumina, lithium disilicate and feldspar, mass ratio 5:3:2 The third layer of inorganic filler Alumina, lithium disilicate and feldspar, mass ratio 6:3:1
[0135] Note: The layers are stacked one after another in the direction from dentin to enamel.
[0136] Embodiment 5:
[0137] This embodiment provides a gradient bionic dental restoration material, based on the gradient bionic dental restoration material in a specific embodiment, wherein:
[0138] The weight ratio of the polymerizable monomer to the multi-layer porous composite ceramic skeleton is 10:90;
[0139] The weight of the initiator is 0.5wt% of the weight of the polymerizable monomer;
[0140] The multi-layer porous composite ceramic skeleton is composed of a two-layer structure, and the mechanical properties gradually increase from the dentin to the enamel;
[0141] The polymerizable monomers are [2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)] dimethacrylate and 2-hydroxy-1,3-dimethacryloxypropane, with a mass ratio of 35:65;
[0142] The initiator is benzoyl peroxide;
[0143] The multi-layer porous composite ceramic skeleton is treated with a silane coupling agent (γ-methacryloxypropyltriethoxysilane) to obtain a modified multi-layer porous composite ceramic skeleton;
[0144] The additive is 2,2'-(2,5-diphenylthio)bis[5-(1,1-dimethylethyl)]benzoxazole (fluorescent agent), and the added amount is 0.1wt% of the total weight of the polymerizable monomer and the multi-layer porous composite ceramic skeleton.
[0145] Among them, the raw materials of the multi-layer porous composite ceramic skeleton are shown in Table 5.
[0146] Table 5
[0147] The first layer of inorganic filler Alumina and zirconium oxide, mass ratio 3:7 The second layer of inorganic filler Alumina and zirconium oxide, mass ratio 7:3
[0148] Note: The layers are stacked one after another in the direction from dentin to enamel.
[0149] Preparation Examples 1-5 respectively provide a preparation method of a gradient bionic dental restoration material. The preparation method refers to the preparation method in the specific implementation manner, and the specific conditions are limited as shown in Table 6.
[0150] Table 6
[0151]
[0152]
[0153] The specific resin solution preparation in step (4) is shown in Table 7.
[0154] Table 7
[0155]
[0156] The performance of the gradient bionic dental restoration materials obtained in Examples 1-5 was tested, and the specific testing method is as follows:
[0157] (1) Porosity
[0158] Place the sample in an oven at 100°C and dry it to constant weight. Weigh the dry mass of the sample at room temperature m1. Boil the sample in boiling water for 2 hours, take it out and cool it to room temperature, then weigh the floating weight of the saturated sample in water m2. Then take it out of the water, gently wipe off the excess water on the surface of the sample with moisture-absorbing gauze, and quickly weigh the wet weight of the saturated sample in the air m3.
[0159] Porosity = (m3-m1) / (m3-m2)
[0160] (2) Flexural strength & elastic modulus
[0161] A 1.2×4.0×16 test piece was prepared and then polished with 2000-grit sandpaper. A three-point bending test was performed using a tensile testing machine at a fulcrum spacing of 12 mm and a crosshead speed of 1.0 mm / min. The average value of ten specimens was used for evaluation.
[0162] (3) Hardness
[0163] Wet-grind the test surface with 2000-grit sandpaper to ensure that the sample surface is smooth. Use Vickers hardness test: select "3" for the test force value and 10s for the holding time; take 5 times at different positions of the sample and take the average value.
[0164] The above test results are shown in Table 8.
[0165] Table 8
[0166]
[0167] The number of layers in the table corresponds to the number of layers of the multi-layer porous composite ceramic skeleton inorganic filler.
[0168] The present invention illustrates the products and detailed methods of the present invention through the above embodiments, but the present invention is not limited to the above products and detailed methods, that is, it does not mean that the present invention must rely on the above products and detailed methods to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the operation of the present invention, addition of auxiliary operations, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A gradient bionic dental restorative material, characterized in that: The raw materials of the gradient bionic dental restoration material include polymerizable monomers, a multi-layer porous composite ceramic skeleton and an initiator; The weight ratio of the polymerizable monomer to the multi-layer porous composite ceramic skeleton is 10:90 to 30:70; the polymerizable monomer is a free radical resin monomer; the free radical resin monomer includes methyl (meth)acrylate, isobutyl (meth)acrylate, benzyl (meth)acrylate, dodecyl (meth)acrylate, 2-(N,N-dimethylamino)ethyl (meth)acrylate, 2,3-dibromopropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, propylene glycol mono(meth)acrylate, glycerol mono(meth)acrylate, erythritol mono(meth)acrylate, N-hydroxymethyl (methyl)acrylate, Acrylamide, N-hydroxyethyl (meth)acrylamide, N-(dihydroxyethyl) (meth)acrylamide, (meth)acryloyloxydodecylpyridinium bromide, (meth)acryloyloxydodecylpyridinium chloride, (meth)acryloyloxyhexadecylpyridinium chloride, (meth)acryloyloxydecyl ammonium chloride, 2-(meth)acryloyloxyethyl dihydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 2-(meth)acryloyloxyethylphenyl hydrogen phosphate, 11-(meth)acryloyloxy-1,1-undecanedicarboxylic acid, 4-(meth)acryloyloxyethoxycarbonylphthalic acid, 10-mercaptodecyl (meth)acrylate, ethylene glycol di(meth)acrylate, Triethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, bisphenol A diglycidyl (meth)acrylate (2,2-bis[4-[3-(meth)acryloyloxy-2-hydroxypropoxy]phenyl]propane), 2,2-bis[4-(meth)acryloyloxyethoxyphenyl]propane, 2,2-bis[4-(meth)acryloyloxypolyethoxyphenyl]propane, 1,2-bis[3-(meth)acryloyloxy-2-hydroxypropoxy]ethane, pentaerythritol di(meth)acrylate, [2,2,4-trimethylhexamethylenebis[ any one of or a combination of at least two of 1,7-diacryloxy-2,2,6,6-tetraacryloxymethyl-4-oxoheptane; The weight of the initiator is 0.01 to 10 wt% of the weight of the polymerizable monomer; The multi-layer porous composite ceramic skeleton is composed of at least two layers, and the mechanical properties gradually increase from the dentin to the enamel. The multi-layer porous composite ceramic skeleton is prepared by the following method, which comprises the following steps: (1) mixing an inorganic filler, a pore-forming agent and a binder to obtain at least two mixed raw materials; wherein the inorganic filler component ratio in each mixed raw material is different; (2) performing a first dry pressing on each of the obtained mixed raw materials independently to obtain a green body; then stacking each green body in sequence, performing a second dry pressing, cold isostatic pressing and sintering in sequence to obtain a multi-layer porous composite ceramic skeleton; The multi-layer porous composite ceramic skeleton is treated with a silane coupling agent to obtain a modified multi-layer porous composite ceramic skeleton.
2. The gradient bionic dental restorative material according to claim 1, characterized in that: The initiator includes any one of dicumyl peroxide, tert-butyl peroxide, benzoyl peroxide, tert-butyl peracetate, cumene peroxide, methyl ethyl ketone peroxide or tert-butyl perbenzoate, or a combination of at least two thereof.
3. The gradient bionic dental restorative material according to claim 1, characterized in that: The gradient bionic dental restoration material further comprises an additive.
4. The gradient bionic dental restorative material according to claim 3, characterized in that: The additives include any one of a crosslinking agent, a fluorescent agent, a bactericide, a colorant, a promoter, an inhibitor, an ultraviolet absorber, an anti-discoloration agent, a viscosity modifier, a wetting agent, an antioxidant, a stabilizer or a diluent, or a combination of at least two thereof.
5. The gradient bionic dental restorative material according to claim 3, characterized in that: The additive is added in an amount of 0 to 5 wt % of the total weight of the polymerizable monomer and the multi-layer porous composite ceramic skeleton.
6. The gradient bionic dental restorative material according to claim 5, characterized in that: The additive is added in an amount of 0.01 to 1 wt % of the total weight of the polymerizable monomer and the multi-layer porous composite ceramic skeleton.
7. A method for preparing the gradient bionic dental restorative material according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) mixing an inorganic filler, a pore-forming agent and a binder to obtain at least two mixed raw materials; wherein the inorganic filler component ratio in each mixed raw material is different; (2) performing a first dry pressing on each of the obtained mixed raw materials independently to obtain a green body; then stacking each green body in sequence, performing a second dry pressing, cold isostatic pressing and sintering in sequence to obtain a multi-layer porous composite ceramic skeleton; (3) impregnating the obtained multi-layer porous composite ceramic skeleton with a silane coupling agent solution to obtain a modified multi-layer porous composite ceramic skeleton; (4) infiltrating the obtained modified multilayer porous composite ceramic skeleton with resin to obtain a resin-infiltrated composite ceramic skeleton; (5) The obtained resin-infiltrated composite ceramic skeleton is cured to obtain a polymer-based infiltrated ceramic composite material.
8. The method for preparing the gradient bionic dental restorative material according to claim 7, characterized in that: The inorganic filler in step (1) includes any one of silicon dioxide, aluminum silicate, sodium aluminosilicate, sodium silicate, potassium silicate, barium silicate, zirconium silicate, aluminum oxide, titanium dioxide, zirconium oxide, fluorine glass, borosilicate glass, sodium glass, barium glass, barium aluminosilicate glass, glass containing strontium or zirconium, glass ceramics, fluoroaluminosilicate glass, calcium fluoride, strontium fluoride, calcium carbonate, titanium oxide, calcium phosphate, hydroxyapatite, calcium hydroxide, strontium hydroxide, sodium feldspar or potassium feldspar, or a combination of at least two thereof.
9. The method for preparing the gradient bionic dental restoration material according to claim 8, characterized in that: The silicon dioxide is fumed silicon dioxide.
10. The method for preparing the gradient bionic dental restorative material according to claim 7, characterized in that: The pore-forming agent includes any one of polyvinyl alcohol, polyvinyl acetate, polyvinyl butyral, polymethyl methacrylate microspheres, polystyrene microspheres or starch, or a combination of at least two of them.
11. The method for preparing the gradient bionic dental restorative material according to claim 7, characterized in that: The raw materials in step (1) are mixed and then ball-milled and dried in sequence to obtain at least two mixed raw materials.
12. The method for preparing the gradient bionic dental restorative material according to claim 11, characterized in that: The rotation speed of the ball mill is 100-900 r / min.
13. The method for preparing the gradient bionic dental restoration material according to claim 11, characterized in that: The ball milling time is 0.5 to 12 hours.
14. The method for preparing the gradient bionic dental restorative material according to claim 11, characterized in that: The drying temperature is 50-110°C.
15. The method for preparing the gradient bionic dental restoration material according to claim 11, characterized in that: The drying time is 12 to 24 hours.
16. The method for preparing the gradient bionic dental restorative material according to claim 7, characterized in that: The pressure of the first dry pressing in step (2) is 2 to 5 MPa.
17. The method for preparing the gradient bionic dental restoration material according to claim 7, characterized in that: The time of the first dry pressing in step (2) is 10 to 60 seconds.
18. The method for preparing the gradient bionic dental restoration material according to claim 7, characterized in that: The blanks in step (2) are stacked in a manner such that the mechanical properties gradually increase from the dentin to the enamel.
19. The method for preparing the gradient bionic dental restoration material according to claim 7, characterized in that: The pressure of the second dry pressing in step (2) is 4 to 10 MPa.
20. The method for preparing the gradient bionic dental restoration material according to claim 7, characterized in that: The time of the second dry pressing in step (2) is 10 to 60 seconds.
21. The method for preparing the gradient bionic dental restoration material according to claim 7, characterized in that: The pressure of the cold isostatic pressing in step (2) is 150 to 300 MPa.
22. The method for preparing the gradient bionic dental restoration material according to claim 7, characterized in that: The cold isostatic pressing time in step (2) is 0.5 to 10 minutes.
23. The method for preparing the gradient bionic dental restorative material according to claim 7, characterized in that: The sintering in step (2) includes a first sintering and a second sintering performed sequentially.
24. The method for preparing the gradient bionic dental restoration material according to claim 23, characterized in that: The heating rate of the first sintering is 2-10°C / min.
25. The method for preparing the gradient bionic dental restoration material according to claim 23, characterized in that: The first sintering temperature is 450-650°C.
26. The method for preparing the gradient bionic dental restoration material according to claim 23, characterized in that: The first sintering heat preservation time is 0.5 to 3 hours.
27. The method for preparing the gradient bionic dental restoration material according to claim 23, characterized in that: The heating rate of the second sintering is 2-10°C / min.
28. The method for preparing the gradient bionic dental restoration material according to claim 23, characterized in that: The second sintering temperature is 700-1300°C.
29. The method for preparing the gradient bionic dental restoration material according to claim 23, characterized in that: The second sintering heat preservation time is 0.5 to 5 hours.
30. The method for preparing the gradient bionic dental restoration material according to claim 7, characterized in that: The silane coupling agent solution immersion in step (3) is carried out under vacuum conditions.
31. The method for preparing the gradient bionic dental restoration material according to claim 7, characterized in that: In step (3), the multi-layer porous composite ceramic skeleton is impregnated with a silane coupling agent solution and then dried to obtain a modified multi-layer porous composite ceramic skeleton.
32. The method for preparing the gradient bionic dental restoration material according to claim 7, characterized in that: The resin liquid used for the resin penetration in step (4) includes a polymerizable monomer and an initiator, and the polymerizable monomer is a free radical resin monomer.
33. The method for preparing the gradient bionic dental restoration material according to claim 7, characterized in that: The resin solution used for the resin infiltration in step (4) also includes additives.
34. The method for preparing the gradient bionic dental restoration material according to claim 7, characterized in that: The resin infiltration in step (4) is carried out alternately under vacuum conditions and normal pressure.
35. The method for preparing the gradient bionic dental restoration material according to claim 7, characterized in that: The holding time of the resin infiltration under vacuum conditions in step (4) is independently 10 to 60 minutes.
36. The method for preparing the gradient bionic dental restorative material according to claim 7, characterized in that: The holding time of the resin infiltration at normal pressure in step (4) is independently 10 to 60 minutes.
37. The method for preparing the gradient bionic dental restoration material according to claim 7, characterized in that: The temperature of the curing treatment in step (5) is 60 to 180°C.
38. The method for preparing the gradient bionic dental restoration material according to claim 7, characterized in that: The pressure of the curing treatment in step (5) is 100 to 300 MPa.
39. The method for preparing the gradient bionic dental restorative material according to claim 7, characterized in that: The curing treatment time in step (5) is 1 to 10 hours.
